1997
DOI: 10.1017/s0021859696004121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term waterlogging applied at various growth phases on growth, development and yield in Vigna unguiculata

Abstract: The effects of short-term waterlogging during the vegetative, reproductive and total growth phases were investigated in four cultivars of cowpea (Vigna unguiculata L. Walp) in relation to their controls in a pot experiment conducted at the University of the West Indies, St. Augustine, in 1989. All cultivars were able to recover completely and produce near to normal yields, when waterlogging was confined to the vegetative period. Recovery growth was affected in cultivars waterlogged during the total growth phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 3 publications
2
10
0
4
Order By: Relevance
“…The other genotypes were less affected and the rate of reduction was about 7% in GK-7, GK-48, IPSA-13, IPSA-15, BARI mung-5 and the lowest was in VC-6173A (3.91%). Similar result in reduction in seed size of waterlogged copwpea cultivars was found by Umaharan et al (1997). The functional relationship (r =0.78) between 1000-seed weight and seed yield plant -1 of 4 days waterlogged plants showed exponential association (Fig.…”
Section: Seed Weightsupporting
confidence: 80%
See 1 more Smart Citation
“…The other genotypes were less affected and the rate of reduction was about 7% in GK-7, GK-48, IPSA-13, IPSA-15, BARI mung-5 and the lowest was in VC-6173A (3.91%). Similar result in reduction in seed size of waterlogged copwpea cultivars was found by Umaharan et al (1997). The functional relationship (r =0.78) between 1000-seed weight and seed yield plant -1 of 4 days waterlogged plants showed exponential association (Fig.…”
Section: Seed Weightsupporting
confidence: 80%
“…The highest percentage of reduction over control treatment in pod plant -1 was recorded in GK-65 (52.94%) followed by GK-7 (46.03%) and the lowest was in BARI mung-5 (13.68%). Umaharan et al (1997) ) showed almost linear and becomes exponential when plant had more than 8.00 pods plant -1 (Fig. 1).…”
Section: Resultsmentioning
confidence: 94%
“…Rapid recovery in root dry weight could be seen after removal of waterlogging. Umaharan et al (1997) found that the root dry weight increased in response to waterlogging during vegetative phase in cowpea. During 10 days recovery period, root dry weight from initial sample was reduced in the treatment T 3 (4-day waterlogged and received 25 kg K ha ).…”
Section: Root Dry Weightmentioning
confidence: 97%
“…The soil water potential in the deep layers was around -5 kPa, which is a partly anaerobic condition for some of the species examined, such as common millet, pearl millet, foxtail millet, maize, barley, and oat, according to the criteria of Kono et al (1987) and . Sinha (1980) and Umaharan et al (1997) also observed the negative effects of waterlogging on the shoot and root development of pigeon pea and cowpea. Therefore, the wet soil condition in deep soil should be one of the main causes of species-specifi c responses in terms of water uptake from deep and wet soil under drought in the topsoil layer.…”
Section: Water Uptake From Deep Soil Layersmentioning
confidence: 98%